2x-(5x+2)=9x-26

Simple and best practice solution for 2x-(5x+2)=9x-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-(5x+2)=9x-26 equation:


Simplifying
2x + -1(5x + 2) = 9x + -26

Reorder the terms:
2x + -1(2 + 5x) = 9x + -26
2x + (2 * -1 + 5x * -1) = 9x + -26
2x + (-2 + -5x) = 9x + -26

Reorder the terms:
-2 + 2x + -5x = 9x + -26

Combine like terms: 2x + -5x = -3x
-2 + -3x = 9x + -26

Reorder the terms:
-2 + -3x = -26 + 9x

Solving
-2 + -3x = -26 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-2 + -3x + -9x = -26 + 9x + -9x

Combine like terms: -3x + -9x = -12x
-2 + -12x = -26 + 9x + -9x

Combine like terms: 9x + -9x = 0
-2 + -12x = -26 + 0
-2 + -12x = -26

Add '2' to each side of the equation.
-2 + 2 + -12x = -26 + 2

Combine like terms: -2 + 2 = 0
0 + -12x = -26 + 2
-12x = -26 + 2

Combine like terms: -26 + 2 = -24
-12x = -24

Divide each side by '-12'.
x = 2

Simplifying
x = 2

See similar equations:

| 3y-5=-8(6+5t) | | 11(t-3)+3t=7(2t+4)-10 | | 4x-7=-2x-19 | | 8.99(85)=650+x | | 6+25x=20x+8 | | 8(x-5)-6x=-26 | | 0.5x(y-z)= | | 5.45=14.8-2.2t | | -22=4w+2(w+4) | | y+24=11 | | 7(3x+6)=21x-10 | | (p+7)(-2)= | | -33=5(v-3)-2v | | x=-1/2*4 | | 8.99(x)=1050+335 | | -(3r-2)=-4-4r | | -5y+8=10+y | | x+3-3(5x+15)=5 | | -4+3x=-6+10x | | 12x^2y^4-3x^5+9x^3y^2=0 | | 6x+234= | | -x+33=2x+15 | | a=(3x^2y^3)(5xy^2) | | -3(1-2x)=47-x | | Solve-3(2x-9)=-3 | | 4x+6y=-132 | | 3-2x=5(3+x) | | 6+2x=2x+6 | | 9n-7=4n+8 | | 10x-50+50=-15+50 | | 23-4x=7-8x | | 12x=18-2x |

Equations solver categories